Environmental Drivers of Plankton Backscattering Strength (SV) in Tunda Island's Marine Ecosystem, Banten - Nuswantari, Farras Taqy Alya; Pujiyati, Sri; Solikin, Steven; Hestirianoto, Totok; Hisyam, Muhammad (Journal of Fisheries and Environment, 2024)
Plankton play a crucial role in pelagic ecosystems, serving as a primary food source in marine food webs and influencing nutrient cycling. Hydroacoustic methods are effective for detecting targets such as plankton by generating backscatter values, which indicate their distribution. This approach provides insights into their horizontal and vertical distribution. This research aimed to map and analyze the spatial and temporal distribution of plankton volume backscattering strength (SV) values ​​using hydroacoustic methods, and to examine the relationship between these SV values ​​and environmental parameters in the waters around Tunda Island, Banten. Data collection included oceanographic measurements: temperature, salinity, DO, pH, currents and water clarity, as well as acoustic data. Oceanographic data were gathered from 16 sampling points at the water surface around Tunda Island. The relationship between oceanographic parameters and acoustic data was analyzed using Principal Component Analysis (PCA). The study found that temperatures around Tunda Island ranged from 28 to 30.2 °C, salinity from 30.3 to 33.5‰, pH from 8.1 to 8.4, DO from 6.39 to 7.67 mg·L-1, water clarity from 9.57 to 34.36%, and currents from 0.13 to 0.69 m·s-1. The SV for horizontal plankton distribution ranged from -82.04 to -76.06 dB, while vertical distribution ranged from -82.04 to -75.07 dB. PCA analysis showed that the relationship between plankton distribution and aquatic parameters accounted for 57.2% of the cumulative variance, with each parameter making either a positive or negative contribution. This research provides baseline data on plankton abundance and environmental conditions in Tunda Island’s waters, highlighting the use of hydroacoustic methods for detecting fine-scale distribution patterns in relation to ecological variables. The findings contribute valuable insights into plankton ecology in areas impacted by anthropogenic activity, supporting future ecological monitoring, fisheries management, and resource conservation efforts.